OCCURRENCE OF CIRRHOSIS AND PRIMARY LIVER CANCER IN AN ESKIMO POPULATION HYPERENDEMICALLY INFECTED WITH HEPATITIS B VIRUS - SKINHØJ, PETER; HANSEN, JENS P. HART; NIELSEN, NILS HØJGAARD; MIKKELSEN, FLEMMING (Oxford University Press, 1978)
Hepatitis type B is hyperendemic in Greenland with serologic evidence of infection In 54% of adults and a hepatitis B surface antigen (HBsAg) carrier rate of 7–25%. The Impact of this infection rate on the occurrence of cirrhosis and primary liver cancer (PLC) was studied. Mortality rates for cirrhosis were obtained from official mortality statistics, 1951–1975. PLC was identified by a study of all biopsy and necropsy material taken in the study area during the same period. Neither cirrhosis nor PLC was found to be a more prevalent cause of death in this population than in Northern Europe where hepatitis B Is at least 10-fold less prevalent. It is concluded that hepatitis B infection per se does not contribute significantly to the development of cirrhosis or to PLC, at least in the Eskimo population of Greenland.